The Role of Interpretation of Socio-Cultural Verses in Mutual Cooperation as a Solution to the Urban Environmental Crisis - Nurfadilah, Aninda; Riadin, Ahmad; Hakim, Lukmanul; Hermanto, Edi (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This verse emphasizes the importance of faith and knowledge as elements that elevate a person's status in the sight of Allah. In Islam, knowledge is not only understood as theoretical insight but must also be actualized through practices aligned with Sharia guidelines. This study employs a qualitative approach with a thematic exegesis method to analyze the relationship between knowledge, action, and etiquette in Islam, highlighting etiquette as a crucial element in the learning process. While previous studies have largely discussed Q.S. Al-Mujadilah verse 11 in the context of the virtue of seeking knowledge, this article places special emphasis on the importance of applying knowledge in daily life. The application of knowledge is deemed essential in shaping noble character, aligned with the goals of national education. Through a review of classical and contemporary exegesis literature, this article concludes that an ideal learning process must be accompanied by etiquette and righteous deeds. This aims to ensure that knowledge does not remain mere theoretical understanding but also provides tangible benefits to individuals and society. Thus, the learning process becomes more holistic, encompassing intellectual, spiritual, and moral aspects. This conclusion supports the view that the integration of knowledge, action, and etiquette is a fundamental pillar in realizing the goals of Islamic education. Such an education is expected to produce individuals who are faithful, knowledgeable, and morally upright, in accordance with Islamic teachings and the nation's noble values.